La importancia de la cultura estética para desarrollar la motricidad fina en los estudiantes de tercer año de educación general básica de la escuela Club Rotario de la ciudad de Latacunga - Cajas Sinchiguano, Diana Cristina (2017)
The plastic expression is an important aspect that should be made known to both parents and teachers on how to improve the fine motor development of children from 4 to 5 years to allow them to express their creativity, safety, stimulate Linguistic and communication intelligence, the development of sensory - motor thinking, logical, graphic, facilitate the initiation of mathematics and writing, the expression of their feelings and emotions, the satisfaction of sharing and participating in team and respect for each other. The proposal was a didactic workshop for parents to take into account the importance that should be given to the plastic expression, for that was taken into account each of the themes and sub-themes involved in both plastic expression As in the fine motor skills of the children because we must know each definition of the topic raised, focused the research with field data and documentaries of the socio-educational field in which the research was developed, the population that was taken into account are the Children of the third year of Basic Education School Rotary Club, also disclosed the independent variable that is the plastic expression and all the techniques that was used and the dependent variable that is the fine motor, development and components of said variable And lastly, the resources and budgets that were used for the support of bibliographic research were taken into account.